IMPLEMENTATION BIRTH PLANNING AND COMPLICATIONS PREVENTIONS PROGRAM (P4K) ON COASTAL COMMUNITIES IN MAMUJU - Ashriady Ashriady; Satriani G. Satriani G.; Nurdiana Nurdiana (FORIKES, 2017)
The results of the 97 countries, there is a significant correlation between aid delivery with maternal mortality (Depkes, 2011). Proportion of birth in Indonesia showed 76.1% in Healthcare Facilities and 23.7% in home and another (Kemenkes RI, 2014). In the coastal community primary choices deliveries take place at home, assisted by shamans because mothers feel safe from evil spirits, and convenient for the family attended (Yunarti, 2013). Scope of delivery assistance by health workers in 2006 - 2011 in West Sulawesi has not reached the target of minimum service standards in 2015 by 90%, obstetric complications handled in 2011 in Mamuju 35.1%. The aim of research to analyze the implementation of Birth Planning and Complications Preventions Program (P4K) based on the knowledge and attitude of Mother on Coastal Communities in Mamuju. This type of research is survey with cross sectional study design. In the study period in August-October 2016. The population is all Mother toddler who visited IHC 330, 149 of the samples obtained by using the formula, taken by accidental sampling method. The results showed 68 (81.9%) of respondents have sufficient knowledge of the implementation of the less well P4K, 113 (79.6%) positive attitude to the implementation mother P4K less good, there is no statistical relationship between knowledge and attitude of mothers with implementation P4K. Midwives need intensive assistance in filling and installation sticker P4K at home mom.